The Impact of Service Quality and Brand Image on Customer Satisfaction and Its Consequences on Customer Loyalty, Banco Nacional Comercio Timor-Leste, Suai Branch - Silvester Ferreira; Basuki Rachmat (PT. Berkah Digital Teknologi, 2024)
Purpose of the study — This research aims to investigate the impact of service quality and brand image on customer satisfaction and its subsequent effects on customer loyalty at Banco Nacional Comercio Timor-Leste, Suai Branch. Research method—A quantitative descriptive approach was employed, utilizing surveys distributed to customers who have been clients for at least three years. The data was analyzed using Partial Least Squares (PLS) structural equation modeling. Result— The findings indicate a weak influence of service quality and brand image on customer satisfaction (R-Square = 0.185), while customer satisfaction, along with these variables, significantly contributes to customer loyalty (R-Square = 0.487). Conclusion— The study concludes that enhancing service quality and brand image is crucial for improving customer satisfaction, which in turn fosters customer loyalty. Practical implications include recommendations for the bank to refine service strategies to meet customer expectations effectively.